Rice yogurt with various beans fermented by lactic acid bacteria from kimchi - Choi, Yeon Hwa; Han, Myung Joo (Food science and biotechnology, 2022)
In this study, the rice yogurt with various beans was developed using a mixture of rice saccharification solution as an artificial sweetener substitute and bean milk as a milk substitute. Rice yogurt was fermented with lactic acid bacteria isolated from kimchi. The lactic acid bacteria count in rice yogurt with various beans had the highest range of 9.37- 9.54 log CFU/g at 12 h fermentation. Also, at 12 h fermentation, pH ranged from 4.05 to 4.20. Rice yogurt with seoritae had the highest brix (15.52°Bx) and DPPH radical scavenging activity (41.86%). In the sensory evaluation, rice yogurt with seoritae received high preference scores in most categories, including flavor, sweet taste, sour taste, mouthfeel and overall preference. These findings suggest that the optimum fermentation time may be 12 h, and rice saccharification solution is an appropriate sugar substitute. Seoritae milk is suitable for the development of rice yogurt with beans.